Contribuições para a gestão ambiental do Rio Capivara no Alto Sertão Sergipano - Santos, José Alberto (2017)
The semi-arid region is a Brazilian region where water resources are limiting to ecological systems, because they are intermittent, present only during rainy periods. Despite being a region with limitations, it presents several urban conglomerates, which leads the aquatic environments to the accumulation of a great load of nutrients, making aquatic ecosystems eutrophized. The objective of this work is to evaluate the main anthropogenic impacts in the region and their effects on the water quality of the Capivara River. Four sampling collections were carried out along the river in three points: at the source, at the confluence with the Riacho do Cachorro, which drains the effluents from Monte Alegre city and the last at the mouth, where the river Capivara flows In the São Francisco River, in Porto da Folha, during the periods of rain and drought, the study occurred in one of the period of low rainfall and poor distribution, the river always remained with water, at the source because it is dammed, at the confluence due to the evictions Of the sewers of the city and at the mouth, due to the influence of the São Francisco River. The temperature, conductivity, dissolved oxygen, total dissolved solids, turbidity and pH were analyzed with a multiparameter probe, as well as collected samples and taken to the laboratory for physical, chemical and biological analysis of the main parameters:, Apparent Color, Ammoniac Nitrogen , Nitrate, Nitrite, Sulfate, BOD, COD, Metals and Coliforms. The analyzes made it possible to verify that the waters of the Capivara River are very polluted, with values well above that established by the National Council for the Environment (CONAMA) 357/05 and State Law 5858/06, Especially after receiving the Cachoeiro Creek, which drains the sewage of Monte Alegre. Concomitant with the analysis, we listened to the riverside population through a semi structured questionnaire to evaluate the environmental perception.